HopBA1, a pathogen virulence factor, reveals tissue-specific immune responses within the Pseudomonas syringae pv. tomato–Nicotiana benthamiana pathosystem - Todd, Tyler Scott, author; Nishimura, Marc, advisor; Sloan, Dan, committee member; Roberts, Robyn, committee member (Colorado State University. Libraries, 2024)
Plant pathogens represent a major threat to food security as they dramatically reduce crop yield, impact the expression of desirable traits, and reduce post-harvest longevity. To infect host plants, bacteria like Pseudomonas syringae pv. tomato DC3000 (Pst DC3000) utilize a type III secretion system to deliver virulence proteins (also known as effectors) into the host cytoplasm to suppress immunity. In response, plants have evolved intracellular immune receptors that perceive immunosuppression and reactivate immunity. Thus, a given pathogen effector can both suppress and activate immunity depending on the host genome. Dissecting the molecular mechanisms of plant pathogen effectors helps inform our understanding of both disease and resistance. The present work reveals an uncharacterized role for Pst DC3000 as an aggressive vascular pathogen, causing systemic infection in the model plant Nicotiana benthamiana (Nb). Further, it establishes that the bacterial effector HopBA1 inhibits movement through the vascular system, despite increasing pathogen persistence within the primary infection site in leaves. Simultaneously, HopBA1 was found to induce irreversible upward vertical bending (i.e., hyponasty) in the petioles of infiltrated leaves, a novel phenotype for a bacterial effector. LC-MS/MS and RNA-Seq revealed phytohormone alteration (notably, a reduction in auxin and jasmonic acid-related metabolites) and transcriptional reprogramming of both developmental and defense genes. HopBA1-dependent growth restriction was suppressed in Nb eds1 (ENHANCED DISEASE SUSCEPTIBILITY 1) mutant plants, which still undergo HopBA1-induced hyponasty. Together, these results suggest that (1) HopBA1 triggers tissue-specific immune responses and (2) hyponasty is due to HopBA1's virulence activity, rather than host immune activation. Thus, HopBA1 in combination with the model pathogen Pst DC3000 becomes an important tool to dissect the poorly understood area of vascular-specific immunity. Vascular pathogens are particularly devastating and difficult to manage in crop species owing to the pathogen's internal location and systemic route of infection, making this research useful in crop improvement.
Keywords: Nicotiana benthamiana; plant-pathogen interactions; vascular immunity; plant pathology; effector-triggered immunity; Pseudomonas syringae